Naruszewiczowy przekład dzieł Tacyta - Bober-Jankowska, Magdalena (Colloquia Litteraria, 2020)
Adam Naruszewicz, one of the most prominent representatives of the Polish Enlightenment, is remembered as a great poet, historian, journalist, and also as a translator. He is the author of one of the greatest achievements in the field of translation of this period: Kaja Korneliusza Tacyta dzieła wszystkie Przekładania Adama Stanisława Naruszewicza S.J. (Complete Works of Gaius Cornelius Tacitus: Translated by Adam Stanisław Naruszewicz, S.J.) Volume I (1772) and Volume II (1773), which included The Annals (Annales), while Volume III (1776) included The Histories (Historiae). Volume IV (1783) consisted of The Germania (De origine et situ Germanorum), Agricola (Dvita et moribus Iulii Agricolae), Dialogues (Dialogus de oratoribus) and the supplements to Volume II.